Xerocomellus carmeniae (Boletales, Basidiomycota), a new fungus from northeastern Mexico - Garza-Ocañas, Fortunato; García Jiménez, Jesús; Guevara-Guerrero, Gonzalo; Martínez-González, César Ramiro; Ayala-Vásquez , Olivia; de la Fuente, Javier Isaac (Instituto de Ecología, A.C., 2022)
Background and Aims: Xerocomellus is a genus of the Boletaceae family, characterized by the small to medium, boletoid to gastroid basidiomata, usually with areolate pileus, and smooth to ornamented basidiospores. So far only two species are known from Mexico. The aim of this study is to describe a new species of Xerocomellus, based on morphological, molecular and ecological data. Methods: Sampling of studied specimens was carried out in Nuevo León state, northeastern Mexico (2009 and 2016). Classic protocols for macrofungi were followed. Hand cut sections of specimens were made and mounted in KOH and Melzer reagent to observe microstructures. The identification of the putative host tree was made in the botanical herbarium CFNL of the Facultad de Ciencias Forestales, Universidad Autónoma de Nuevo León; the type of forest was identified according to field observations and satellite images. DNA was extracted from three different collections. The ITS region and the gene LSU were obtained and analyzed. The material was deposited in the mycological collections of the herbaria “José Castillo Tovar” (ITCV) of the Instituto Tecnológico de Ciudad Victoria and CFNL. Key results: Xerocomellus carmeniae differs from other Xerocomellus species by the following combination of characteristics: boletoid basidiomata, reddish areolate pileus, yellowish stipe, and basidiospores of 10.5-13.6 × 5.7-7.8 µm, elongate, sometimes truncate. Conclusions: Xerocomellus carmeniae is the third species of this genus known from Mexico and is putatively associated to Quercus cambyi. Some specimens show an aberrant form, but more studies are recommended to evaluate a possible transition to a secotioid form.